Effect of Auxins on Rooting Behaviour of Neem (Azadirachta indica) Branch Cuttings - Singh, R. R.; Chander, Harish (Indian Forester, 2001)
The performance of auxins on rooting behaviour of Neem cuttings was studied in glasshouse at Department of Forestry, CCS HAU, Hisar. Root was absent in all types of branch cuttings under control after 30 days. Emergence of root was observed in soft-wood cuttings treated with IBA (500 and 1000 ppm), IAA (500 ppm) IBA+IAA (500 ppm) and IBA+IAA+2, 4+D (500 ppm and 1000 ppm), but it was very low ranging from 3.3 to 6.7 %. In semi-hardwood cuttings, 3.3% cuttings treated with 500 ppm of IBA and 500 ppm ofIBA+IAA+2, 4+D concentrations rooted after 30 days planting. Maximum rooting percentage was observed in softwood cuttings treated with 500 ppm ofIBA (33.3 %) followed by the 500 ppm ofIAA (23.3 %) and semi hard wood cuttings treated with 500 ppm of IBA (23.3 %). At 90 days after planting, maximum number of roots was observed in softwood cuttings treated with 500 ppm of IBA (11.63 %) followed by 500 ppm of IAA (6.67%).